2002
DOI: 10.1086/338352
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Turbulence in Solar Modeling

Abstract: The general consensus is that in order to reproduce the observed solar p-mode oscillation frequencies, turbulence should be included in solar models. However, until now there has not been any well-tested efficient method to incorporate turbulence into solar modeling. We present here two methods to include turbulence in solar modeling within the framework of the mixing length theory, using the turbulent velocity obtained from numerical simulations of the highly superadiabatic layer of the sun at three stages of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 31 publications
3
67
0
Order By: Relevance
“…The systematic growth in error at higher frequencies (higher n) is associated with the inherent uncertainties in the modeling of the superadiabatic layer of the Sun via the mixing-length theory. Li et al (2002) have shown that much of this discrepancy can be eliminated by incorporating the results of numerical stellar convection in both the model and the p-mode frequency calculation (see also Rosenthal et al 1999;Robinson et al 2003). We assume that the stellar model frequency uncertainties are similar to the discrepancies found between our solar model frequencies and the observed frequencies.…”
mentioning
confidence: 63%
“…The systematic growth in error at higher frequencies (higher n) is associated with the inherent uncertainties in the modeling of the superadiabatic layer of the Sun via the mixing-length theory. Li et al (2002) have shown that much of this discrepancy can be eliminated by incorporating the results of numerical stellar convection in both the model and the p-mode frequency calculation (see also Rosenthal et al 1999;Robinson et al 2003). We assume that the stellar model frequency uncertainties are similar to the discrepancies found between our solar model frequencies and the observed frequencies.…”
mentioning
confidence: 63%
“…A stronger foundation for interpreting helioseismic data (e.g. Stein & Nordlund 2001;Li et al 2002) and inferring the abundances of various elemental constituents of the sun (e.g. Asplund et al 2005;Caffau et al 2008) are benefitting tremendously from this work: these almost brute force approaches to solar surface convection are offering sufficiently precise information about interior structure to shed light on deeper astrophysical conundrums including the formation scenario of the sun (Guzik & Mussack 2010) and, in combination with solar neutrino observations, standard model physics (Serenelli et al 2009).…”
Section: The Current Framework For Computing Evolutionmentioning
confidence: 99%
“…A method to incorporate the effects of turbulence into the outer layers of one-dimensional (1D) stellar models has been implemented in YREC (Li et al 2002). The method requires a detailed three-dimensional hydrodynamical simulation (3D RHD) of the atmosphere and highly superadiabatic layer of stars (Robinson et al 2003).…”
Section: Turbulencementioning
confidence: 99%
“…1 and Fig. 2 for the case of a solar model, taken from the work of Li et al (2002). In the Li et al (2002) paper, the p-mode frequencies for two calibrated solar models that include the effects of turbulence are compared to the standard solar model (ssm) p-mode frequencies.…”
Section: Frequency Corrections To Solar P-modesmentioning
confidence: 99%
See 1 more Smart Citation